Empirical analysis of 5 DSE equity traded through IDLC Investments Ltd & portfolio management - Ismail, Mohammed (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.